Dampak Konservatisme Auditor terhadap Manajemen Laba dan Opini Going Concern pada Perusahaan Bursa Efek Indonesia - Vienna Tanisya; Budi Harsono (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This research aims to determine the effect of the quality of earnings management relationship auditors on Going Concern opinions in companies listed on the IDX for the 2016-2020 period. The quantitative method uses secondary data from independent auditor reports and the annual financial reports of non-manufacturing companies listed on the IDX for the 2016-2020 period. This research used a purposive sampling method with a sample of 690 from 789 companies with a final number of 3171, resulting in observation data. Data was tested using Eviews software. The dependent variable is in the form of Business Continuity Opinion. The independent variable is Profit Management. Moderating variables are Big 4. Control variables are the Market value of company assets, Firm size, Leverage, ROA, Market book ratio, Company age, Sales growth and CFO. The research results show that the Quality of the Auditor hasn’t a significant relationship with Earnings Management. Then Earnings Management cannot strengthen a significant relationship between the Profit Managemen and the Going Concern opinion. Thus, testing on 11 variables only creates 1 variable in line with the hypothesis, namely, the Big 4 variables have a significant negative relationship to Earnings Management. Profit Management variable testing has no significant relationship to the Going Concern opinion.